2020
DOI: 10.1021/acs.jpcb.0c09915
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Understanding of Homogeneous Nucleation of CO2 Hydrates Using Transition Path Sampling

Abstract: Carbon dioxide hydrate is a solid built from hydrogen-bond stabilized water cages that encapsulate individual CO 2 molecules. As potential candidates for reducing greenhouse gases, hydrates have attracted attention from both the industry and scientific community. Under high pressure and low temperature, hydrates are formed spontaneously from a mixture of CO 2 and water via nucleation and growth. Yet, for moderate undercooling, i.e., moderate supersaturation, studying hydrate formation with molecular simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 52 publications
4
33
0
Order By: Relevance
“…For bulk methane hydrate, it has been shown that nucleation can proceed through direct crystallization from a solid nucleus or through transformation of an amorphous phase first appearing in the solution (46,47). The observation of these two processes-either one-step crystallization or two-step crystallization through the formation of an amorphous phase-was shown to depend on temperature with the two molecular mechanisms competing at moderate undercooling (32).…”
Section: Resultsmentioning
confidence: 99%
“…For bulk methane hydrate, it has been shown that nucleation can proceed through direct crystallization from a solid nucleus or through transformation of an amorphous phase first appearing in the solution (46,47). The observation of these two processes-either one-step crystallization or two-step crystallization through the formation of an amorphous phase-was shown to depend on temperature with the two molecular mechanisms competing at moderate undercooling (32).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, path sampling-based techniques such as transition path sampling (TPS) [42][43][44] , transition interface sampling (TIS) [45][46][47] and forward flux sampling (FFS) 10,20,21,48,49 all allow for the direct calculation of nucleation rates. Interestingly, until quite recently not many examples of any of these methodologies being applied to the calculation of J could be found in the literature, most likely due to the high computational cost associated with converging these algorithms.…”
Section: A the Tools At Our Disposalmentioning
confidence: 99%
“…Forward-Flux Sampling (FFS) in particular has become the principle workhorse of many rare event studies 10,143 . Alternative techniques such as transition interface sampling (TIS) are also used in the context of nucleation 43 , but generally acknowledged to be somewhat more complex to implement. The aimless shooting approach to path sampling is a third example 144 , used in a number of nucleation studies 122 .…”
Section: G Slow Dynamicsmentioning
confidence: 99%
“…At high driving force, the CO 2 hydrates are known to nucleate into amorphous polymorphs in which the 4 1 5 10 6 2 cage type is most abundant. 8,9 At higher pressures (6-18 kbar), another stable crystalline hydrate structure can form, characterized by helicoidal channels. 10 Precise knowledge of the molecular kinetics of formation of these (synthetic) hydrates allows a better control of this process.…”
Section: Introductionmentioning
confidence: 99%
“…The height of this barrier is determined by the liquid-solid surface tension and the driving force. The barrier height can easily be many times the thermal energy, rendering the nucleation an unlikely, or rare, event 9,[12][13][14] to observe computationally. Only due to rare thermal fluctuations, a nucleus of a size corresponding to the free energy maximum, the so-called critical nucleus, emerges.…”
Section: Introductionmentioning
confidence: 99%